PONGKA PADANG AS A TRACE OF THE DANCE OF ELLO-ELLOQ IN KAYU ANGIN, MAJENE - Sahajuddin, Sahajuddin (Walasuji : Jurnal Sejarah dan Budaya, 2021)
The dance of ello-elloq is a traditional dance which was born during the period of Pongka Padang and became a part of tradition in Kayu Angin, Majene Regency. Because the dance was interesting to reveal its traces in Mandar history, this study aimed to explain the traces of the dance of ello-elloq in Mandar history. The method used was history which explained the research problems based on the historical perspectives, starting from the heuristic process, source criticism, interpretation, historiography. The study result showed that the dance of ello-elloq was a traditional dance with a particular meaning for the formation of the unities in Ulunna Salu Mandar due to the historical traces of Pongka Padang. The dance of ello-elloq hunt the historical and cultural reality of Mandar at the time, especially in Kayu Angin. In this area, Pongka Padang and Torije’ne were considered as Mandar anchestors and the dance of ello-elloq was a part of the history of Pongka Padang as well as the starting point for the development of cultural values in Kayu Angin community in Mandar. The cultural values in the dance of ello-elloq were the value of obedience and loyalty through the votive of Pongka Padang, the value of communication between tradition and reality, and the value of gratitude and entertainment.